2020
DOI: 10.7150/jca.46898
|View full text |Cite
|
Sign up to set email alerts
|

EPAS1 targeting by miR-152-3p in Paclitaxel-resistant Breast Cancer

Abstract: Background: Paclitaxel plays a pivotal role in the chemotherapy of breast cancer, but resistance to this drug is an important obstacle in the treatment. It is reported that microRNA-152-3p (miR-152-3p) is involved in tamoxifen resistance in breast cancer, but whether it is involved in paclitaxel resistance in breast cancer remains unknown. Materials and methods: We examined the expression of miR-152-3p in breast cancer tissues and cells by qRT-PCR. After transfecting paclitaxel-resistant MCF-7/TAX cells with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…41 miR-152-3p and PFTK1 were selected as downstream molecules of hsa_circ_102229 based on studies showing that miR-152-3p and PFTK1 are associated with breast cancer. 42,43 In the present study, PFTK1 was confirmed as a direct target of miR-152-3p. In line with the previous results of above studies, overexpression of PFTK1 could compromise the inhibitory effects of hsa_circ_102229, suggesting that hsa_circ_102229 could promote the proliferation, migration and invasion of TNBC cells by regulating PFTK1.…”
Section: Discussionsupporting
confidence: 65%
“…41 miR-152-3p and PFTK1 were selected as downstream molecules of hsa_circ_102229 based on studies showing that miR-152-3p and PFTK1 are associated with breast cancer. 42,43 In the present study, PFTK1 was confirmed as a direct target of miR-152-3p. In line with the previous results of above studies, overexpression of PFTK1 could compromise the inhibitory effects of hsa_circ_102229, suggesting that hsa_circ_102229 could promote the proliferation, migration and invasion of TNBC cells by regulating PFTK1.…”
Section: Discussionsupporting
confidence: 65%
“…Based on the 289 OXPHOS-related gene matrix obtained from the research of Zihao Xu, we used differential expression analysis and identified 66 OXPHOS-related DEGs, including 54 upregulated genes and 12 downregulated genes; most of them have been reported to be associated with cancer. For instance, EPAS1 could enhance the effect of paclitaxel on breast cancer cells by inhibiting growth and promoting apoptosis of MCF-7/TAX cells ( Song et al, 2020 ). Furthermore, functional annotation of the OXPHOS-related DEGs also indicated that the candidate genes were significantly related to ATP metabolic process, purine ribonucleoside triphosphate metabolic process, and the essential pathways reported in many cancers ( Matsuda et al, 2017 ; Fallah and Rini, 2019 ), including retrograde endocannabinoid signaling and HIF-1 signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Hence protecting endothelial cells can maintain the integrity of BBB. The function of miR-152-3p to modulate apoptosis in cancers has been well established [29,30]. Recent years, the anti-apoptotic effect of miR-152-3p in injury diseases have received increasing investment.…”
Section: Discussionmentioning
confidence: 99%